Vicinity and Flee (as Exemplified in Pre-Islamic Poetry): Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Aiad aqumer, Lect (lark, 2022)
: Pre-Islamic poetry has no doubt been a dark era to most readers, where ignorance, dissoluteness, libertinism, polytheism, cruelty, tribalism, retaliation, fanaticism, and raids dominated life. On the other hand, there were love, peace, coexistence, high ideals, wisdom, reasoning, and anti-oppressionism. This paper, accordingly, emphasizes vicinty as a key area of analysis. Elaborating on social and psychological aspects of relevant poems, this paper unfolds vicinity, questions its importance, and indicating how it contributed to coexistence and interest in life. The paper draws on analytical approach as a model.